Hiperglikemia pada Pasien Diabetes Melitus Tipe 1 dan 2 yang Menjalani Puasa Ramadan : Laporan Kasus - Ahdi, Iwal Reza; Sasiarini, Laksmi (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Background: Ramadan fasting is an obligation for every Muslim, including Muslim patients who suffer from diabetes mellitus. The most common complication in diabetic patients when fasting is hypoglycemia, but in special conditions, hyperglycemia can also occur, and even emergency occurs in both type 1 and type 2 diabetes patients. Purpose: To know the hyperglycemia complications in type 1 and 2 diabetes mellitus in Ramadhan fasting Methods: Reported a case of inpatient diabetes mellitus 1 and 2 who underwent fasting during Ramadan and complications of hyperglycemia occurred in dr. Saiful Anwar Hospital (RSSA) Malang during the month of Ramadan Results: Both patients experienced hyperglycemia which was a response to an increase in response to hypoinsulinemia in type 1 diabetes and an increase in glycogenolysis in DM type 2. Conclusion: Hyperglycemia can occur in patients with type 1 and 2 DM who fast during the month of Ramadan